Analisis Tingkat Efisiensi Industri Tekstil Dan Produk Tekstil di Indonesia Kurun Waktu 2007 - 2009 - Sarastri mumpuni Ruchba; Billy Didik Permana (Unisia, 2013)
In the manufacturing industry, textile and textile products (TPT) industry become one of the biggest contributors to the Gross Domestic Product (GDP) of Indonesia, while the manufacturing industry itself is the largest contributor to GDP. However, the Indonesian textile industry in recent years has many problems, among others, the raw material (cotton) were 99.5% imported, textile machinery production average age was 20 years and over, and port charges are expensive. Therefore, this paper aims to analyze the efficiency of the textile industry in Indonesia. The textile industry is divided into three classifications according to the criteria of ISIC, i.e. the textile industry (ISIC 17), the apparel industry (ISIC 18), leather and leather goods industry (ISIC 19). The method of analysis used is the Data Envelopment Analysis (DEA) by using Variable Return to Scale (VRS) dan Constant Return to Scale (CRS). The analysis shows that in general the level of efficiency of textile and textile products in Indonesia is still low. In 2009 the level of efficiency of the textile industry in Indonesia is the highest compared to 2007 and 2008.Keywords: Level of Efficiency, Industrial Textile, Garment, Leather and Leather Goods Industry, Data Envelopment analysis (DEA), Variable Return to Scale (VRS)